2004
DOI: 10.1159/000079932
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Increased Enzymuria in Different Morphological Forms of Glomerulonephritis

Abstract: Background: High urinary excretion of lysosomal enzymes is thought to reflect tubulointerstitial damage and is observed both in the acute and chronic phases of various morphological forms of glomerulonephritis (GN). It is related to the degree of proteinuria and secondary interstitial inflammatory process. N-acetyl-β-D-glucosaminidase (NAG) and β-glucuronidase (β-GR) are the most commonly used markers of tubulointerstitial injury. NAG and β-GR are also contained in azurophilic granulations of polymorphonuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…NAG-B isoenzyme has been used in determining the source of increased enzymuria. Contrary to NAG, released also from degranulated neutrophils [1,2], NAG-B specifically originates from the kidney [13]. In our study the NAG and NAG-B excretion was significantly higher in AGR and ATN groups than in SGF patients; the highest NAG and NAG-B excretion was observed in the AGR group.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…NAG-B isoenzyme has been used in determining the source of increased enzymuria. Contrary to NAG, released also from degranulated neutrophils [1,2], NAG-B specifically originates from the kidney [13]. In our study the NAG and NAG-B excretion was significantly higher in AGR and ATN groups than in SGF patients; the highest NAG and NAG-B excretion was observed in the AGR group.…”
Section: Discussioncontrasting
confidence: 49%
“…Most extensively studied markers include a lysosomal enzyme-N-acetyl-b-D-glucosaminidase (NAG), which is released mainly from the proximal tubule epithelial cells, but also from degranulated leucocytes [1,2], its tubule-specific isoenzyme NAG-B, brush border enzymes-alanylaminopeptidase (AAP) and c-glutamyltransferase (GGT) [3][4][5], a-glutathione-S-transferase (a-GST) originating from proximal tubule cells cytoplasm, and p-GST originating from distal tubule cells [6,7]. Among various LMWP, retinol binding protein (RBP) and b 2 -microglobulin (b 2 M) have been measured to assess reabsorptive and catabolic functions of the tubules.…”
Section: Introductionmentioning
confidence: 99%
“…As in the present study, a report on urinary enzymes in humans with glomerulonephritis also demonstrated a correlation between uNAG/c and proteinuria and the absence of an association between uNAG/c and sCr. 44 The current hypothesis is that urinary enzymes correlate better with tubulointerstitial damage than with an indirect measurement of glomerular filtration rate such as sCr.…”
Section: Discussionmentioning
confidence: 85%
“…Of note, both NAG‐A and B are detectable in healthy cats . Although present in the serum and other tissues and cells, urinary NAG, GGT, and ALP originate from the renal tubules in the absence of glomerular damage …”
Section: Renal Biomarkers: Urinementioning
confidence: 99%